MGB–KGB Agencies in Occupied Lithuania - Žemaitienė, Nijolė (Genocidas ir rezistencija, 1997)
The Soviet occupation created a pretext for a part of society to collaborate with the occupying power. Alongside the open supporters of the occupying power, a whole army of secret collaborators – MGB–KGB agents – emerged. Espionage and ideological indoctrination of the population is a prerequisite for the existence of a totalitarian system. The two totalitarian ideologies of this century differed fundamentally only in the fact that the fascist ideology gave priority to physical destruction, while the communist ideology – to mental subjugation.